Linking between soil properties, bacterial communities, enzyme activities, and soil organic carbon mineralization under ecological restoration in an alpine degraded grassland - Shu, Xiangyang; Hu, Yufu; Liu, Weijia; Xia, Longlong; Zhang, Yanyan; Zhou, Wei; Liu, Wanling; Zhang, Yulin (Frontiers in Microbiology, 2023)
Soil organic carbon (SOC) mineralization is affected by ecological restoration and plays an important role in the soil C cycle. However, the mechanism of ecological restoration on SOC mineralization remains unclear. Here, we collected soils from the degraded grassland that have undergone 14 years of ecological restoration by planting shrubs with Salix cupularis alone (SA) and, planting shrubs with Salix cupularis plus planting mixed grasses (SG), with the extremely degraded grassland underwent natural restoration as control (CK). We aimed to investigate the effect of ecological restoration on SOC mineralization at different soil depths, and to address the relative importance of biotic and abiotic drivers of SOC mineralization. Our results documented the statistically significant impacts of restoration mode and its interaction with soil depth on SOC mineralization. Compared with CK, the SA and SG increased the cumulative SOC mineralization but decreased C mineralization efficiency at the 0–20 and 20–40 cm soil depths. Random Forest analyses showed that soil depth, microbial biomass C (MBC), hot-water extractable organic C (HWEOC), and bacterial community composition were important indicators that predicted SOC mineralization. Structural equal modeling indicated that MBC, SOC, and C-cycling enzymes had positive effects on SOC mineralization. Bacterial community composition regulated SOC mineralization via controlling microbial biomass production and C-cycling enzyme activities. Overall, our study provides insights into soil biotic and abiotic factors in association with SOC mineralization, and contributes to understanding the effect and mechanism of ecological restoration on SOC mineralization in a degraded grassland in an alpine region.